Modeling and computer simulation of bow stabilization in the vertical plane - Zanevskyy, I. (International Journal of Sports Science and Engineering, 2008)
The aim of the research is to develop a method of mechanical and mathematical modeling and computer simulation of dynamic stabilization of bow rotation in the vertical plane intending to get practical recommendations for the sport of archery. Behavior of a flexible stabilizer in the main plane of the modern sport bow designed in the frame of International Archery Federation is analyzed using a mechanical and mathematical model. The model is designed basing on Euler-Bernoulli beam and Lagrange equations of the second kind. An engineering oriented method based on virtual modes and Rayleigh-Ritz procedure is developed to study natural frequencies of the archer-bow-stabilizer system. The results of modeling of the archer-bow-arrow system correlate with well-known results of a high-speed video analysis: the process of common motion has a significant non-linear character.